Comparative Study on the Corro-Erosive Properties of Base Cemented Transition Metals TaC and HfC and TaX-HfX-C Coatings - C. H. Ortiz; S. S. Sanchez; J. C. Caicedo; W. Aperador; Jorge Sánchez-Molina; J. Bautista Ruiz (Metals, 2022)
In this research, we report on a comparative study of the corro-erosive properties of TaC and HfC individual coatings and (Ta70-Hf30-C) and (Ta30-Hf70-C) coatings. These were subjected to different impact angles of abrasive particles, corresponding with angles of 30°, 60° and 90°. It was determined that at 90°, a higher structural damage of the coatings obtained was presented. In addition, for all the systems, it was possible to conclude that the coating formed by (Ta30-Hf70-C) presented a roughness of approximately 7.11 nm, which influenced corrosive properties such as the corrosion potential and corrosion rate. Finally, it was possible to conclude that the (Ta30-Hf70-C) coating presented a higher resistance against corro-erosive environments. This was attributed to structural and mainly superficial factors, making this coating the best option to be implemented as a protective coating against highly aggressive environments in industry.